Web-based realistic mathematics learning environment for 21st-century skills in primary school students - Lisnani; Putri, Ratu Ilma Indra; Zulkardi; Somakim (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
This study aims to develop a valid, practical, and which has potential effect web-based realistic mathematics learning environment with the six cultural contexts of the island of Sumatera. The learning environment has the potential to positively impact primary school students. The study employed design research method, which encompassed the preliminary, design, and assessment stages using the Kirkpatrick model. The research subjects consisted of three model teachers and 57 fourth-grade students. Research data was collected through observation, documentation, questionnaires, interviews, and tests. The web-based learning environment's validity level was found to be very high, with a score of 3.32, while practicality was rated at 3.86. The potential effects of the environment on mathematics learning were also deemed to be significant, with a score of 77.35. It was designed to facilitate the teaching and learning of mathematics by the PMRI approach, with a focus on topics such as numbering, geometry, and measurement, while also developing 21st-century skills.